UNFOLDING THE SPA INDUSTRY: SPA BUSINESS MODELS TROUGH THE PRODUCT LIFE CYCLE - Javier Vázquez-Illa Navarro (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 1970)
This article pursues inspiring theory building that helps in the understanding of spas. The industry’s life cycle is subject to examination to ascertain its predominant business model. Employed methodologies are literature review, study of a sample of European and American spas, and case study research on a European spa company. The amenity spa is singled out as the prevalent business model: its value proposition offers a more comprehensive experience than the traditional destination spa. The consequences of the present model’s choices: high amortization and fixed costs, besides market confusion, are highlighted as the industry enters its early maturity stage, after two decades of growth. Future prospects are optimistic, though, due to the linkage of spas with well-rooted social trends, provided incumbents fine-tune their competitive strategies and implement more efficient operations. The spa industry’s partial nonconformity to the product life cycle theory remains unresolved and will require further research.